Reabilitação em disfagia orofaríngea neurogênica: sabor azedo e temperatura fria - Cola, Paula Cristina [UNESP]; Gatto, Ana Rita [UNESP]; Silva, Roberta Gonçalves da [UNESP]; Schelp, Arthur Oscar [UNESP]; Henry, Maria Aparecida Coelho de Arruda [UNESP] (CEFAC Saúde e Educação, 2008)
TEMA: reabilitação em disfagia orofaríngea neurogênica OBJETIVO: apresentar revisão de literatura sobre os controles neurofisiológicos da deglutição orofaríngea e a influência do sabor azedo e da temperatura fria no mecanismo da deglutição. CONCLUSÃO: quanto à questão do controle central da deglutição, ainda existem controvérsias em relação ao sabor azedo e a temperatura fria. Esses dois parâmetros provocam mudanças na dinâmica da deglutição, podendo trazer benefícios aos indivíduos acometidos por disfagia orofaríngea neurogênica. Porém, tais achados sugerem a necessidade de investigações futuras com populações randomizadas.

BACKGROUND: rehabilitation in neurogenic oropharyngeal dysphagia PURPOSE: to submit an overview of the related literature about neurophisiological control of oropharingeal dysphagia and the role of temperature and sour taste on swallowing mechanisms. CONCLUSIONS: as for the neurophysiologic swallowing control, there are still controversies when it comes to sour taste and cold temperature. These two standards can change the swallowing dynamics, and they may bring out benefits to the individuals with neurogenic oropharyngeal dysphagia. Therefore, the findings suggest the need for further investigations with randomized studies.
Rehabilitation in neurogenic oropharyngeal dysphagia: sour taste and cold temperature
Keywords: Transtornos de Deglutição; Reabilitação; Acidente Cerebral Vascular; Deglutition Disorders; Rehabilitation; Stroke